A quantitative analysis of hydroxyl radical generation as H2O2 encounters siderite: Kinetics and effect of parameters. (March 2021) - Sun, Fuwei; Chen, Tianhu; Zou, Xuehua; Liu, Haibo; Chu, Ziyang; Shu, Daobing; Wang, Hanlin; Huang, Fangju; Chen, Dong
Abstract: Siderite is a conventional mineral of sedimentary rock and can activate H2 O2 to produce hydroxyl radicals (·OH). Bisphenol A (BPA), 2, 4-dichlorophenoxyacetic acid (2, 4-D), and sodium sulfadiazine are selected as typical micropollutants to be degraded in a siderite-activated H2 O2 system. To determine the influence of solution chemistry on siderite-activated Fenton-like reactions, the amount of ·OH was quantified by using benzoic acid as a probe molecule, and then, kinetic fitting was used to analyze the reaction rate. The results showed that in the range of pH values from 3 to 9, the dissolved Fe 2+ and the lattice Fe(Ⅱ) of siderite activate H2 O2 to generate ·OH. An increase in siderite dosage and H2 O2 concentration favored the generation of ·OH, but higher siderite dosage and H2 O2 concentration suppressed the production rate. The inhibition order of anions on the generation of ·OH was confirmed as follows C l − > N O 3 − > S O 4 2 − . Little difference was observed in the presence of Ca 2+ and Mg 2+, while the presence of Mn 2+ significantly promoted the production of ·OH. The suppression of humic acid (HA) became more serious as the HA concentration increased. Cycling experiments proved that the system could still produce ·OH in four cycles, although the production rate experienced a slight decrease. The experimental results suggested the role of siderite in the degradation of organic pollution in the process of in-situ soil and groundwater remediation. Graphical abstract: Image 1 Highlights: Siderite effectively activate H2 O2 to produce ·OH over a wide pH values range. Siderite has a high potential to remove micropollutants (MPs) in subsurface with H2 O2 . The detailed kinetic fitting describes the influence of parameters. The role of lattice Fe(Ⅱ) in activating H2 O2 is demonstrated.